Hubungan Pengetahuan Sikap Ibu dan Dukungan Keluarga dengan Penggunaan Kontrasepsi IUD - Eva Norita; Hasbiah Hasbiah; Rizki Amalia (Universitas Batanghari Jambi, 2022)
The Intra Uterine Device (IUD) is a small, elastic plastic device that is inserted into the uterus. The IUD or IUD is placed for 5 to 10 years, depending on the type or until the woman wants the device removed. This study aims to determine the relationship, attitudes and family support with the use of IUD contraception at the Beringin Health Center, Kec. Lubai Kab. Muara Enim 2021. The design of this research is an Analytical Survey using a cross sectional research design. The population in this study were all third trimester pregnant women who had their pregnancy checked in January-July 2021, namely 35 respondents and the number of samples was 35 respondents. The sampling technique used is Accidental Sampling. Data analysis used chi square statistical test with a value of 0.05. The results of the study from 35 respondents were obtained based on the relationship between knowledge P value = 0.01, attitude P-value = 0.01 and family support P-value = 0.03 with the use of IUD contraception. From the results of this study, researchers provide advice to midwives to maintain and improve counseling methods for family planning acceptors, especially in the selection of IUD contraception.